2007
DOI: 10.1105/tpc.107.055319
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis FIERY1, XRN2, and XRN3 Are Endogenous RNA Silencing Suppressors

Abstract: The eukaryotic defense response posttranscriptional gene silencing (PTGS) is directed by short-interfering RNAs and thwarts invading nucleic acids via the RNA slicing activity of conserved ARGONAUTE (AGO) proteins. PTGS can be counteracted by exogenous or endogenous suppressors, including the cytoplasmic exoribonuclease XRN4, which also degrades microRNA (miRNA)-guided mRNA cleavage products but does not play an obvious role in development. Here, we show that the nuclear exoribonucleases XRN2 and XRN3 are endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
394
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(430 citation statements)
references
References 61 publications
25
394
0
5
Order By: Relevance
“…3B, Middle), similar to that described previously in a study based on the infection of a different xrn4/ein5 mutant by a different CMV isolate (40). We found that ein5 plants were also more resistant to CMV-Δ2b than WT plants and that CMVΔ2b accumulated to the highest level in rdr1 plants (Fig.…”
Section: Detection Of a Distinct Class Of Arabidopsis Sirnas Induced supporting
confidence: 89%
“…3B, Middle), similar to that described previously in a study based on the infection of a different xrn4/ein5 mutant by a different CMV isolate (40). We found that ein5 plants were also more resistant to CMV-Δ2b than WT plants and that CMVΔ2b accumulated to the highest level in rdr1 plants (Fig.…”
Section: Detection Of a Distinct Class Of Arabidopsis Sirnas Induced supporting
confidence: 89%
“…In animals, some of these complexes are associated with components of the RNA silencing machinery (Leung et al, 2006), and there is evidence that Drosophila P-bodies are involved in miRNA-directed target decay through deadenylation and decapping, whereas translational repression is P-body independent (Eulalio et al, 2007). In plants, components of the RNA decapping machinery were found involved in RNA silencing (Gazzani et al, 2004;Gy et al, 2007), and the existence of P-bodies was recently demonstrated (Xu et al, 2006). Thus, it will be interesting to investigate which type of proteins, such as other members of the large AGO family, are linked to miRNAs and their mRNA targets in nonpolysomal fractions.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] The accumulation of miR164 does not decrease in the xrn4 null mutant. 48 It is thought that the lethality of dcp1, dcp2 and vcs arise from defects in decapping and subsequent 5'-3' mRNA decay, although the null xrn4 mutant is not lethal.…”
Section: Introductionmentioning
confidence: 96%
“…[46][47][48] The accumulation of miR164 does not decrease in the xrn4 null mutant. 48 It is thought that the lethality of dcp1, dcp2 and vcs arise from defects in decapping and subsequent 5'-3' mRNA decay, although the null xrn4 mutant is not lethal. [46][47][48] Our results suggest that defects in the miRNA pathway are a major cause of the lethal phenotypes in dcp1, dcp2 and vcs mutants.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation